2011
DOI: 10.1039/c1jm10195a
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured donor/acceptor interfaces in photovoltaic cells using columnar-grain films of a cross-linked poly(fluorene-alt-bithiophene)

Abstract: We report on the fabrication of photovoltaic cells, PVs, with controlled donor/acceptor interfaces using a process based on the phase separation between a cross-linkable polyfluorene and polystyrene. Robust, nanostructured columnar-grain layers of a conjugated cross-linked polymer, F8T2Ox1 (an oxetane-functionalized derivative of poly(9,9-dioctylfluorene-alt-bithiophene)) are obtained after removal of polystyrene. These layers are used, in combination with 1-(3-methoxycarbonyl)propyl-1phenyl-(6,6)C 61 (PCBM) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Farinhas et al used the polymer F8T2Ox1 with reactive oxetane groups. [132] Drees et al introduced cross-linkable fullerenes with glycidol esters of PCBM. [133] Kim et al [134] and Griffini et al [135] used UV cross-linkable bromo-alkyl side chains ( Figure 7) and showed an increased thermal stability in the power conversion efficiency ascribed to stabilization of the morphology.…”
Section: The Active Layermentioning
confidence: 99%
“…Farinhas et al used the polymer F8T2Ox1 with reactive oxetane groups. [132] Drees et al introduced cross-linkable fullerenes with glycidol esters of PCBM. [133] Kim et al [134] and Griffini et al [135] used UV cross-linkable bromo-alkyl side chains ( Figure 7) and showed an increased thermal stability in the power conversion efficiency ascribed to stabilization of the morphology.…”
Section: The Active Layermentioning
confidence: 99%
“…[146,148,150,151,154] Nanopatterning of the interface can be realized by codeposition a crosslinking polymer and another incompatible material followed by removing the latter one, [150,151] or nanoimprinting (include using molds, photolithography etc.) before crosslinking of the underlayer polymer, [148] or just patterning the downside buffer layer before deposition of the donor and acceptor layers.…”
Section: Other Ll Solution Processing Techniquesmentioning
confidence: 99%
“…Moreover, upon crosslinking, the polymer layer is morphologically frozen and becomes more resistant to temperature variations or other influences, which is a key issue in determining the OPV stability. [149,150] The crosslinkers should be designed to meet the following requirements. First, the crosslinking units should be small in size and efficient enough to freeze the film morphology with low amount, which will reduce the influence on the stacking of the original conjugated polymers in order to maintain high charge mobility and light absorption.…”
Section: Other Ll Solution Processing Techniquesmentioning
confidence: 99%
“…[18][19][20] In this respect, a range of crosslinkable conjugated polymers have been developed as promising candidates for interfacial modifi cation. Conventional approaches to prepare crosslinkable conjugated polymers are chemically tethering functional groups such as oxetane groups, [ 21 ] alkyl-bromide, [ 22 ] azide, [ 23 ] and vinyl, [ 24 ] into the polymer chains. Based on these copolymers, crosslinked fi lms can be achieved through the crosslinking reactions triggered by either thermal or ultraviolet light.…”
mentioning
confidence: 99%